Valores séricos de urea, creatinina y ácido úrico en pacientes de 23 a 42 años. - Mendoza Ipiales, Sara Beatriz (Machala : Universidad Técnica de Machala, 2019)
Biochemical analysis is of great importance to verify the health status of a person. The purpose of this research is to compare the serum values of urea, creatinine and uric acid in patients of 23 and 42 years of urban parishes in Cuenca in relation to the patients of the Ángela Loayza de Ollague Obstetric Hospital belonging to the Santa Rosa Canton. In 2014 in Guayaquil and in 2017 in Cuenca, studies were conducted to determine the serum values of these three parameters. A descriptive analytical study was carried out and the qualitative-quantitative method was used: qualitative because 75 fasting blood samples were obtained in the Hospital Clinical Laboratory and quantitative because their results were tabulated by means of the SPSS 24 statistical program that allows determining minimum, maximum and standard deviation of the analytes studied obtaining and average value of urea was 16.8106 mg/dL with a standard deviation of 5.8892 mg/dL with a minimum value of 8.1 mg/dL and a maximum value of 32.4 mg/dL, for creatinine the average value was 0.632 mg/dL with a standard deviation of 0.1861 mg/dL with a minimum value of 0.4 mg/dL and a maximum value of 1.1 mg/dL, while for uric acid the average value was 3.52 mg/dl with a standard deviation of 1,023 mg/dL with a minimum value of 2.10 mg/dL and a maximum value of 6.55 mg/dL, 100% of the patients were women, these values were compared according to the Human comercial house.
El análisis bioquímico es de gran importancia para verificar el estado de salud de una persona. La presente investigación tiene como finalidad comparar los valores séricos de urea, creatinina y ácido úrico en pacientes de 23 y 42 años de las parroquias urbanas de Cuenca en relación con los pacientes del Hospital Obstétrico Ángela Loayza de Ollague del Cantón Santa Rosa. En el año 2014 en Guayaquil y en el 2017 en Cuenca, se realizaron estudios para determinar los valores séricos de estos tres parámetros. Se realizó un estudio analítico descriptivo y se utilizó el método cuali-cuantitativo: cualitativa porque se obtuvieron 75 muestras sanguíneas en ayunas en el Laboratorio Clínico del Hospital y cuantitativa porque sus resultados fueron tabulados mediante el programa estadístico SPSS 24 que permite determinar mínimos, máximos y desviación estándar de los analitos estudiados obteniendo como valor promedio de urea fue 16,8106 mg/dL con una desviación estándar de 5,8892 mg/dL con un valor mínimo de 8,1 mg/dL y un valor máximo de 32,4 mg/dL, para la creatinina el valor promedio fue de 0.632 mg/dL con una desviación estándar de 0,1861 mg/dL con un valor mínimo de 0,4 mg/dL y un valor máximo de 1,1 mg/dL, mientras que para el ácido úrico el valor promedio fue de 3,52 mg/dL con una desviación estándar de 1,023 mg/dL con un valor mínimo de 2,10 mg/dL y un valor máximo de 6,55 mg/dL, el 100% de los pacientes fueron mujeres, estos valores se compararon de acuerdo a la casa comercial Human.
Keywords: VALOR DE REFERENCIA; UREA; CREATININA; ACIDO URICO